Blood integrin- and cytokine-producing T cells are associated with stage and genetic risk score in age-related macular degeneration - Rijken, Rianne; Pameijer, Els M.; Gerritsen, Bram; Hiddingh, Sanne; Stehouwer, Marilette; de Boer, Joke H.; Imhof, Saskia M.; van Leeuwen, Redmer; Kuiper, Jonas JW (Academic Press, 2025)
Age-related macular degeneration (AMD) remains a leading cause of vision loss in the geriatric population. There are age-related changes in peripheral blood leukocyte composition, but their significance for AMD remains unclear. We aimed to determine changes in immune cell populations in the blood of AMD patients. A standardized 31-parameter flow cytometry analysis was conducted on peripheral blood mononuclear cells from 59 patients with early and advanced AMD and 39 controls without AMD, all older than 65 years. Fundus photography and optical coherence tomography were used to classify disease stages and a custom genotype array was used to compute an AMD genetic risk score based on 52 AMD disease risk variants (GRS-52). A generalized linear regression model corrected for age, sex, and smoking status revealed that AMD patients showed decreased frequencies of CD4+ T helper cell population expressing Integrin Alpha E (CD103) (Padj = 0.019). We further noted that early AMD was characterized by increased interleukin-4 (IL-4)-producing CD4+ T helper cells (Padj = 0.013; <0.001), as well as IL-4-producing cytotoxic CD8+ T cells (Padj = 0.016; <0.001). Reclassification of samples based on the GRS-52 revealed that IL-17-producing T cells decreased incrementally across GRS-52 categories. In AMD, alterations in peripheral blood leukocyte populations are associated with genetic risk score and disease stage and include specifically IL-4 and IL-17A cytokine-producing and CD103 integrin-expressing T cell populations.
Keywords: Age-related macular degeneration; CD103; Flow cytometry; GRS-52; Interleukin-17; Interleukin-4; Peripheral blood; T cells; Ophthalmology; Sensory Systems; Cellular and Molecular Neuroscience